Electrochemical studies of steel rebar corrosion in clay: Application to a raw earth concrete. (15th May 2020) - Eid, Joanna; Takenouti, Hisasi; Ait Saadi, Bachir; Taibi, Said
Highlights: Clay-steel interaction for earth concrete use is investigated. Electrochemical methods are used: potentiodynamic voltammetry and EIS. Clay's type doesn't have a significant influence on the corrosion rate of steel rebar. The average corrosion rate value is 3 μm/year. It is acceptable. Reinforcing raw earth concrete with steel rebar is feasible. Abstract: Reinforcement feasibility of a new ecological earth concrete was examined. Steel rebar corrosion, when in contact with three different types of clayey soil, was investigated using electrochemical methods, potentiodynamic voltammetry and impedance spectroscopy (EIS). Results have shown that the voltammetry method overestimates the corrosion rate while EIS supplies the most reliable results. Corrosion rate decreased and a steady state was reached after four months of contact. The type of clay does not have a significant influence on the corrosion rate of the steel rebar, and the average value of 3 μm /year was considered acceptable for the lifetime of the structure.